2008
DOI: 10.1021/ef7005673
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Investigation of Carbon Deposition and Sulfur Evolution in Chemical Looping Combustion with Syngas

Abstract: Chemical looping combustion (CLC) with syngas, a synthesized gas mixture of CO, H 2 , CO 2 , H 2 O(g), N 2 , and H 2 S, was investigated using thermodynamic simulation, with focus on carbon deposition and sulfur evolution in CLC. Five metal oxides, such as NiO, CuO, Fe 2 O 3 , Mn 3 O 4 , and CoO, were selected as oxygen carriers for CLC application. Different influencing factors on the formation of carbon deposits were investigated, including pressure, fuel reactor (FR) temperature, oxygen excess number Φ (den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 20 publications
1
71
0
Order By: Relevance
“…Moreover, other factors like kinetics of sulfur compounds can affect the sulfur gas product distribution in the CLC system predicted by thermodynamics. Finally, it is important to note that the conclusions found by Jerndal et al [3] and Wang et al [18] Up to now, the effect of sulfur on the performance of Fe-based oxygen carriers in continuous CLC units has not been studied yet. In this sense, more tests in continuous facilities are needed to gain an adequate understanding of the behavior and usefulness of these particles for this kind of combustion technology.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, other factors like kinetics of sulfur compounds can affect the sulfur gas product distribution in the CLC system predicted by thermodynamics. Finally, it is important to note that the conclusions found by Jerndal et al [3] and Wang et al [18] Up to now, the effect of sulfur on the performance of Fe-based oxygen carriers in continuous CLC units has not been studied yet. In this sense, more tests in continuous facilities are needed to gain an adequate understanding of the behavior and usefulness of these particles for this kind of combustion technology.…”
Section: Introductionmentioning
confidence: 98%
“…Jerndal et al [3] and Wang et al [18] concluded that there was no risk of iron sulfide or iron sulfate formation under usual CLC process conditions in terms of temperature, concentration of sulfur-containing gases or oxygen excess. However, previous works in our research group [19,20] found that the fate of sulfur in a CLC process could not be predicted based only with thermodynamic analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel materials have received more attention due to its higher reactivity and thermal stability. Wang et al [27] studied the carbon formation and the effect of the presence of sulphur in the syngas, and they found that the pressurized conditions led to more solid carbon and sulphur species deposited on the OC. Also, some experimental data at pressurized conditions can be found.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon deposited oxygen carrier particles can contribute to producing CO as described Eq. (6) in the H 2 generation process (Ishida et al, 1998;Jerndal et al, 2006;Wang et al, 2008), lowering the purity of H 2 .…”
Section: Reduction and Oxidation Behavior Of Chemical Looping Operatimentioning
confidence: 99%
“…The combustion of syngas was noticeable for experiment conducted at 400°C, and reached 100% for experiments conducted at temperatures higher than 500°C. Based on the thermodynamic analysis by previous researchers (Wang et al, 2008;Li et al, 2010), CO and H 2 can be completely converted to CO 2 and H 2 O through the exothermic reaction with Fe 2 O 3 (or Fe 2 TiO 5 ) at temperatures ranging from 200 to 1200°C. However, the reaction rates for experiments conducted at 400°C (or lower) might be too slow to reach equilibrium conversion.…”
Section: Effect Of Reaction Temperature On Co 2 Yield and H 2 Generationmentioning
confidence: 99%